The Role of Mustafa Kemal Ataturk in Establishing the Republic of Turkey - Fernanda Putra Adela (International Journal on Social Science, Economics and Art, 2019)
Before becoming a republic, Turkey was the last Islamic dynasty called the Ottoman Turks. The territory of the Ottoman Turks was very broad which made it a force respected by the international community, especially European countries. The technological advances that occurred in Europe were not in line with what happened in the Ottoman Turks which resulted in this sultanate becoming weak and left behind from more advanced European countries. Moving on from situations and conditions like this, a military officer who had a sense of nationalism came and initiated a republic to replace the Islamic government system which was considered old-fashioned and unable to bring the country into progress like European countries. This desire finally manifested itself through various means of struggle and movement which was quite long and led him to become the first leader of the Republic of Turkey which he formed.